PERAN GAWAI MOBILE DALAM MENDUKUNG LAYANAN INFORMASI PERPUSTAKAAN DIGITAL YANG TERPERSONALISASI - Sugiono, Shiddiq (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2021)
Personalized information service is an information service delivered by digital libraries so that users can only get information according to their needs online. This article is a conceptual study that examines the role of mobile devices as technology to support personalized information services from the aspects of user data collection and service delivery. Data obtained through literature review of scientific articles that have relevance to the main concept. The results showed that mobile devices have a role in sending data and accessing library services efficiently. As a two-way communication medium, mobile devices can send various forms of feedback to the library which eventually become data for further analysis. As for service access, mobile devices can support mobile applications so that there are several traditional services that can be accessed online anywhere and anytime. Not only data in the form of text, technological developments have been able to analyze data in other types, one of which is in the form of voice. The development of technology in the 4.0 industrial revolution has also become an aspect that encourages efficiency because it can bring about automation in the aspects of data collection and access to library services.